Krill oil treatment ameliorates lipid metabolism imbalance in chronic unpredicted mild stress-induced depression-like behavior in mice - Zhang, Hao; Liu, Xiaofang; Li, Bo; Zhang, Yi; Gao, Hua; Zhao, Xianyong; Leng, Kailiang; Song, Zhenhua (Frontiers in Cell and Developmental Biology, 2023)
The pathology of depression involves various factors including interaction between genes and environment.The deficiency of n-3 polyunsaturated fatty acids (n-3 PUFAs) in the brain and depressive symptoms are closely related. Krill oil contains abundant amounts of n-3 PUFAs incorporated in phosphatidylcholine. However, the effect of krill oil treatment on depressive-like behaviors induced by chronic stress and its molecular mechanism in the brain remain poorly understood. Here, we used a chronic unpredictable mild stress (CUMS) model to evaluate the effect of krill oil on depression-like behaviors and explored its molecular mechanism through lipid metabolomics and mRNA profiles in the whole brain. We observed that CUMS-induced depression-like behaviors were ameliorated by krill oil supplementation in mice. The metabolisms of Glycerophospholipids and sphingolipids were disrupted by CUMS treatments, which were ameliorated after krill oil supplementation. Further analysis found that the differently expressed genes after krill oil supplementation were mainly enriched in the membrane structures and neuroactive ligand-receptor interaction pathway, which may be responsible for the amelioration of CUMS-induced depression-like behaviors. Altogether, our results uncovered the relationship between lipid metabolism and CUMS, provided new strategies for the prevention and treatment of depression.